Association between rs6887695 and 3′-untranslated region polymorphisms within the interleukin-12B gene and susceptibility to autoimmune diseases in Asian and European population: A meta-analysis. (18th May 2016) - Xiao, Jian-Ping; Wang, Xue-Rong; Zhang, Sen; Wang, Hai-Yan; Ye, Lei; Pan, Hai-Feng; Wang, De-Guang
Abstract: Background : The associations between rs6887695 and 3′-untranslated region (3′-UTR) single-nucleotide polymorphisms (SNPs) within interleukin-12B ( IL-12B ) and autoimmune diseases (ADs) remain controversial and inconclusive. The aim of this study was to evaluate the association between IL-12B (3′-UTR A/C and rs6887695 C/G SNPs) and ADs by meta-analysis. Methods : PubMed and EMBASE were exhaustively searched for studies on the association between IL-12B SNPs and ADs. Publication bias was examined by a funnel plot and Egger's test. The robustness of the pooled results was assessed by sensitivity analysis. A fixed- or a random-effects model was applied to calculate the pooled odds ratios (ORs). Results : A total of 34 studies were included in this meta-analysis. The pooled results demonstrated that IL-12B rs6887695 SNPs were significantly associated with the risk of ADs. However, there was no significant association between IL-12B 3′-UTR SNPs and ADs. When the studies were stratified by ethnicity, significant association between IL-12B 3′-UTR SNPs and ADs was observed in both Asian and European population. In addition, allele A within 3′-UTR of IL-12B gene was found to be a protective factor for T1DM, but a risk factor for psoriasis. Conclusion: The IL-12B 3′-UTR and rs6887695 SNPs are associated with susceptibility to ADs.